Cryopreservation of protocorm-like bodies and callus of lady's slipper orchid (Paphiopedilum niveum (Rchb.f.) stein) by vitrification and encapsulation-vitrification - Supornchai Chaireok (Prince of Songkla University, 2016)
Thesis (Ph.D., Biology)--Prince of Songkla University, 2015